793. IRIS WALLISIAE. (September 2014) - Hall, Tony; Seisums, Arnis
Summary A new juno iris for the Flora of Lebanon and Syria, Iris wallisiae T. Hall & Seisums, is described and illustrated. Recent work on the systematics and phylogeny of Iris subgenus Scorpiris is reviewed. The relationship of I. wallisiae with related species, and particularly with I. persica L., is discussed.